2017
DOI: 10.3390/s17030528
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Accuracy of Urban Environmental Quality Assessment Using Geographically-Weighted Regression Techniques

Abstract: Urban Environmental Quality (UEQ) can be treated as a generic indicator that objectively represents the physical and socio-economic condition of the urban and built environment. The value of UEQ illustrates a sense of satisfaction to its population through assessing different environmental, urban and socio-economic parameters. This paper elucidates the use of the Geographic Information System (GIS), Principal Component Analysis (PCA) and Geographically-Weighted Regression (GWR) techniques to integrate various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…The Z-score is a widely used statistical technique that can able to standardize a wide range of data to represent the significant changes across the data. 41 Z-score data normalization has been done using the following formula 42 …”
Section: Methodsmentioning
confidence: 99%
“…The Z-score is a widely used statistical technique that can able to standardize a wide range of data to represent the significant changes across the data. 41 Z-score data normalization has been done using the following formula 42 …”
Section: Methodsmentioning
confidence: 99%
“…Spatial data gathered were aggregated in a Geographic Information System (GIS) using Open Source QGIS software with which it was possible to weigh geographical data with statistical analysis [17] through normalization operations, obtaining empirical models that allow the reading of urban phenomena that contribute to the definition of qualityquantitative indices. Indicators were subsequently used for the elaboration of a multiple linear regression model on SPSS Statistical Analysis Software.…”
Section: Territorial Investigationmentioning
confidence: 99%
“…The focus of our attention on GWR is motivated by numerous studies which have demonstrated its potential in the investigation of spatially varying relationships, including climatology (Brunsdon et al 2001 ; Khosravi and Balyani 2019 ; Wehbe et al 2020 ), health (Lin and Wen 2011 ; Ehlkes et al 2014 ; Weber 2018 ; Hong et al 2018 ; Hasyim et al 2018 ), real estate management (Lu et al 2014 ; Liu et al 2016 ), urban studies (Faisal and Shaker 2017 ; Wang et al 2020 ) and land change analysis (Maimaitijiang et al 2015 ; Dadashpoor et al 2019 ). GWR can also be applied in combination with linear, logistic and poisson regression techniques for various applications and reported in many studies (Nakaya et al 2005 ; Ehlkes et al 2014 ; Mayfield et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%